Novel Evaluation of Fuzzy Fractional Cauchy Reaction-Diffusion Equation. (20th April 2022) - Shah, Nehad Ali; El-Zahar, Essam R.; Dutt, Hina M.; Arefin, Mohammad Asif
Abstract : The present research correlates with a fuzzy hybrid approach merged with a new iterative transform method known as the fuzzy new iterative transform method. With the help of Atangana-Baleanu under generalized Hukuhara differentiability, we show that this system works well by getting fractional fuzzy Cauchy reaction-diffusion equations with the initial fuzzy condition. Fractional Cauchy reaction-diffusion equations play a significant role in diffusion, and instabilities can lead to formation and stabilization. The suggested technique looks at fuzzy set theory to figure out how to solve the fuzzy Cauchy reaction-diffusion equations. In this way, the components can be quickly defined and a couple of numerical solutions with the uncertainty parameter can be found. Several numerical instances are looked at to show how effective and valuable the proposed technique is to see if the given problem will come to a solution. The simulation results show that the fuzzy new iterative transform method is an excellent way to study a proposed model's behaviour precisely and accurately.